DAMPAK GAME ONLINE TERHADAP PERUBAHAN SIKAP DAN MINAT BELAJAR SISWA KELAS IV SDN RANGKAPAN JAYA BARU - Jesica Anggraeni Hasugian; Prayuningtyas Angger Wardhani; Fahrurrozi Fahrurrozi (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
This research aims to find out in depth about the impact of playing online games on changes in student attitudes and interest in learning, both positive and negative impacts. The type of research method used is phenomenological qualitative research, which observes the impact of the phenomenon of online gaming among fourth grade elementary school students on changes in their attitude and interest in learning. The subjects in this finding are fourth grade students of SDN Rangkapan Jaya Baru with a total of 28 students. This research was conducted for 3 meetings at SDN Rangkapan Jaya Baru. The data collection techniques in this study were interviews with teachers, students, and parents of fourth grade students of SDN Rangkapan Jaya Baru in Depok City, questionnaires, and documentation regarding the impact of online games on changes in attitude and interest in learning which were conducted for 3 days. From the results that have been carried out, all fourth grade students of SDN Rangkapan Jaya Baru play online games. With various types of online games that they play. Students in class IV have different frequency and duration of time. The results of this study have a negative and positive impact on changes in student attitudes and interest in learning.